PENGARUH VARIASI KOMPOSISI SERBUK GERGAJI KAYU DAN TEMPURUNG KELAPA TERHADAP KADAR ABU BRIKET ARANG - Rany Puspita Dewi (PROSIDING SNAST, 2018)
Sawdust as byproduct of sawmill industry is not optimally utilized yet as one of biomass energy source. Indonesia has potency of sawdust waste about 2.6 millions m3/year. Same as sawdust, coconut shell also just disposed as a waste. Both of the waste have very big potency to be utilized as raw material of briquettes as one of alternative energy which is renewable and environmentally friendly, because both of them have high caloric value. The research aim is to know the influence of composition variation between sawdust and coconut shell (100%:0%, 75%:25%, 50%:50%) and tapioca flour as an adhesive media with 5% of concentration. Ash content of briquettes is measured by ASTM D-3174 method. Research result showed that with composition 100%:0%, resulted briquettes with ash content about 1,16%. Composition 75%:25%, resulted briquettes with ash content about 1,75%. Composition 50%:50%, resulted briquettes with ash content about 2,64%. It shows a trend that the higher the percentage of the coconut shell is added as the mixture of raw material of briquettes, the higher the ash content of briquettes are produced.